Pharmacological Aspects Of Tea Tree Oil (Tto) And Its Role In Dentistry- A Comprehensive Review - JAIGANESH RAMAMURTHY; LAKSHMI.T (International Journal of Pharma and Bio Sciences, 2011)
Tea tree oil (TTO) is originated from Melaleuca alternifolia of the Myrtaceae family and is also known as ti-tree, ti-trol and melasol. TTO is one of the most used essential oils, and thousands of people swear by its wonderful healing properties.TTO is composed of terpene hydrocarbons, mainly monoterpenes, sesquiterpenes and their associated alcohols. Terpinen-4-ol is a major component of TTO and has been considered the main antimicrobial component of the oil. Tea tree oil is an antiseptic used to fight against the germs. It has also been used to treat cuts, minor burns, athlete’s foot, and insect bites. Studies reveals that it can treat bacterial and fungal skin infections, wound infections, gum infections, acne, head lice, eczema, vaginal yeast infections, colds, pneumonia, and other respiratory illnesses. Hence the aim of the article is to compile the literature based upon its pharmacological aspects and its application in the field of dentistry for benefit of mankind.